BiOBr nanoplates@TiO2 nanowires/carbon fiber cloth as a functional water transport network for continuous flow water purification. Issue 2 (8th December 2016) - Mei, Yan; Su, Yanhui; Li, Zheng; Bai, Shiqi; Yuan, Mengyu; Li, Lu; Yan, Zheng; Wu, Jun; Zhu, Lian-Wen
Abstract : A novel BiOBr@TiO2 /carbon hybrid framework as a continuous flow sunlight water purification system has been reported in the present work. Abstract : A novel BiOBr@TiO2 /carbon hybrid framework as a continuous flow sunlight water purification system has been reported in the present work. The BiOBr@TiO2 /carbon hybrid framework was fabricated via the sequential growth of TiO2 nanowires and BiOBr nanoplates on carbon fiber cloth. TiO2 nanowires interweaved with carbon fibers to form a porous network, while BiOBr nanoplates were arrayed on TiO2 nanowires. The obtained BiOBr@TiO2 /carbon hybrid framework possesses numerous micro/nanochannels between their adjacent one-dimensional building blocks, which can serve as an effective water transport network driven by capillary force. Furthermore, BiOBr@TiO2 /carbon hybrid frameworks exhibit impressive sunlight-driven photocatalytic activity and adsorption ability because of their enhanced sunlight absorption ability, efficient charge separation features, and mesoporous architecture. The excellent reusability and durability of the BiOBr@TiO2 /carbon hybrid frameworks have also been confirmed. A novel BiOBr@TiO2 /carbon hybrid framework based continuous flow sunlight water purification system with a high water purification efficiency (305.6 L h −1 m −2 ) has been constructed in the present work. All the features make the BiOBr@TiO2 /carbon hybrid framework a promising material suitable for water purification.